2006
DOI: 10.1038/sj.sc.3101971
|View full text |Cite
|
Sign up to set email alerts
|

Sleep patterns over 15-day period in rats with spinal cord injury

Abstract: Study design: Experimental, controlled trial. Objectives: The purpose of this study was to evaluate over a 15-day period alterations in sleep pattern of rats after spinal cord injury (SCI). Setting: Federal University of Sa˜o Paulo, Department of Psychobiology. Methods: In total, 20 male Wistar rats were used. The rats were divided in two groups: SHAM and SCI. The rats were submitted to the following procedures: electrode insertion surgery, 24 h duration baseline sleep recording, SCI (level T9) and subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Somatosensory deafferentation could also have a role in the complex spectrum of sleep disturbances observed after spinal cord injury. [37][38][39][40][41][42] In any case, our data are limited to the first few hours after spinal cord injury in a rat animal model with urethane anesthesia, and further investigation should be conducted in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Somatosensory deafferentation could also have a role in the complex spectrum of sleep disturbances observed after spinal cord injury. [37][38][39][40][41][42] In any case, our data are limited to the first few hours after spinal cord injury in a rat animal model with urethane anesthesia, and further investigation should be conducted in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Such an analysis would be extremely important because ferritin is an endothelial reticulum protein responsible for storing iron, and there is a relationship between serum ferritin levels and the amount of iron stored. 17 In previous studies, 7,8 we found increased limb movements during sleep in rats from 4 days after SCI onward. Because the present investigation demonstrated reduced levels of plasma iron in rats 1, 3, 7 and 15 days after SCI, our findings suggest a temporal association between increased limb movements induced by SCI and reduced levels of plasma iron.…”
Section: Discussionmentioning
confidence: 61%
“…In their study, the animals began to present leg movements during sleep at 4 days after SCI. In 2007, Esteves et al 8 analyzed sleep patterns in SCI animals. In addition to experiencing reduced sleep efficiency and an increased number of arousals, the animals presented limb movements that began at 4 days after lesion and remained until the end of the experiment, thus constituting a PLM animal model with SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies in animals have documented dramatic changes in rat muscle myosin heavy-chain (MHC) isoforms after SCI, with a complete reduction in neuromuscular activity leading to atrophy of the skeletal muscle [8,9,10]. Additionally, Esteves et al [11,12] demonstrated that rats exhibited changes in their sleep patterns after SCI, including increased arousals and limb movements during sleep.…”
Section: Introductionmentioning
confidence: 99%